2010
DOI: 10.1038/npp.2010.120
|View full text |Cite
|
Sign up to set email alerts
|

Resequencing of Nicotinic Acetylcholine Receptor Genes and Association of Common and Rare Variants with the Fagerström Test for Nicotine Dependence

Abstract: Common single-nucleotide polymorphisms (SNPs) at nicotinic acetylcholine receptor (nAChR) subunit genes have previously been associated with measures of nicotine dependence. We investigated the contribution of common SNPs and rare single-nucleotide variants (SNVs) in nAChR genes to Fagerström test for nicotine dependence (FTND) scores in treatment-seeking smokers. Exons of 10 genes were resequenced with next-generation sequencing technology in 448 European-American participants of a smoking cessation trial, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 90 publications
(115 reference statements)
4
74
0
2
Order By: Relevance
“…Thus, the FTND score ranged from 0 to 8. The mean FTND (3.4) was within the range of mean scores (2.8-4.6) from 15 general population studies in Europe and the United States (Fagerström & Furberg, 2008) and lower than scores reported in clinical samples (Wessel et al, 2010).…”
Section: Lifetime Measuresmentioning
confidence: 43%
See 1 more Smart Citation
“…Thus, the FTND score ranged from 0 to 8. The mean FTND (3.4) was within the range of mean scores (2.8-4.6) from 15 general population studies in Europe and the United States (Fagerström & Furberg, 2008) and lower than scores reported in clinical samples (Wessel et al, 2010).…”
Section: Lifetime Measuresmentioning
confidence: 43%
“…Although rs16969968 is considered robustly associated with CPD based on meta-analyses in populations of European origin (Furberg et al, 2010;Liu et al, 2010;Saccone et al, 2010), some of the individual data sets within the meta-analyses did not show a significant association between rs16969968 and CPD (e.g., Figure 1 in Saccone et al, 2010). Although previous studies showed an association between rs16969968 and FTND (reviewed in Ware et al, 2012), other studies did not find evidence for this association (Sherva et al, 2010;Wessel et al, 2010); evidence for this association is less robust than for CPD. As additional evidence accumulates from diverse populations with different genetic backgrounds and motivations for smoking, the relationship between rs16969968 and smoking phenotypes may become better understood.…”
Section: Discussionmentioning
confidence: 98%
“…[24][25][26][27][28] These studies come to similar conclusions: that it is not a single variant acting alone that is causal, but rather sets of variants. 24,25,28 The sets they identified are rare variants that overlap with functional annotations such being missense or nonsynonymous variants.…”
Section: Discussionmentioning
confidence: 85%
“…24,25,28 The sets they identified are rare variants that overlap with functional annotations such being missense or nonsynonymous variants. Several of these previous studies focused only on exons, [24][25][26]29 and therefore would have missed 22 out of 27 (81.5%) of the single locus top findings and 23 out of 33 (69.6%) variant set top findings. To our knowledge, none of these previous investigations examined the role regulatory variant sets may play in smoking.…”
Section: Discussionmentioning
confidence: 99%
“…For example, SNPs in CHRNA6 and CHRNB3, the genes encoding the a6 and b3 subunits, have been associated with nicotine dependence, subjective response to nicotine, and self-reported number of unsuccessful quit attempts (Bierut et al 2007;Greenbaum et al 2006;Saccone et al 2007;Zeiger et al 2008;Hoft et al 2009). Additional studies have implicated the gene encoding for the a4 subunit, CHRNA4, in various smoking phenotypes (Breitling et al 2009;Wessel et al 2010;Han et al 2011;Xie et al 2011). Furthermore, polymorphisms in the CHRNA4 gene have been significantly associated with abstinence rates while on nicotine replacement therapy (Hutchison et al 2007) or varenicline (King et al 2012), suggesting a potential role for CHRNA4 as a target for therapeutic intervention.…”
Section: Translational Research In Nicotine Dependencementioning
confidence: 99%